EVALUASI KEBUTUHAN AIR DAN ELEVASI BUKAAN PINTU PADA SISTEM TATA AIR PASANG SURUT UNIT TAMBAN KABUPATEN BARITO KUALA - Febry Asthia Miranti (Jurnal Teknologi Berkelanjutan, 2018)
Rehabilitation efforts were carried out on the tidal system of swamp irrigation area (DIR) at Tamban Unit DIR in Tamban Sari Bangun Village, Barito Kuala Regency in 2013, including installing a water gate with a dimension of 600cmx400cm so that productivity of degraded land could be increased. However, the water gate is not functioning and operationalized by local farmers, so it needs an evaluation of water requirements, and evaluation of the water gate opening. In this study mainstay rainfall analysis, evapotranspiration analysis, irrigation water needs analysis, tidal analysis, evaluation of existing water systems, and simulation using the HEC-RAS program were conducted. The final stage of the study obtained conclusions and suggestions regarding the evaluation of water needs and elevation of water gate openings in the Tamban Unit water system. Based on the calculation of irrigation needs, it is known that the highest water level elevation for land processing is in June I, which is + 9.040m, while the growth period in August I is + 9.060m. From the results of hec-ras simulations it is known that the fulfillment of water in paddy fields (upstream) cannot be fulfilled, because the elevation of paddy fields is too high. While the fulfillment of water needs in the paddy fields (downstream) can be fulfilled in simulation 10, with the elevation conditions of the existing floodgate, the floodgate fully opened, and the tidal hydrograph raised 1.03 times. The water needs are fulfilled if the tides are higher than the measurement results that is 1.03 times.